FACTORS INFLUENCING THE FOREIGN DIRECT INVESTMENT INFLOW IN THE CZECH REPUBLIC - Linhartová, Veronika (My University, 2018)
Foreign direct investment opens new work opportunities, positively influences workforce productivity, introduces the latest findings and technological know-how and positively influences the balance of payments. The aim of the paper is to identify, based on the available literature, the possible factors influencing the inflow of foreign direct investment into the country and, using statistical methods, to identify specific factors influencing the inflow of foreign direct investment into the Czech Republic during the period from 1998 to 2015. Using the multiple regression model, Science and research expenditures, GDP, corporate tax income and the Corruption Perceptions Index have emerged as significant factors. While spending on science and research or the GDP seem to have a positive effect on FDI, corporate tax and Corruption Perceptions Index appear to be negative in the results in the Czech Republic and the analyzed period.
Faktory ovlivňující příliv přímých zahraničních investic do České republiky
Keywords: Foreign direct investment; foreign direct investment inflow; foreign direct investment determinants; multiple regression analysis.; Přímé zahraniční investice; příliv přímých zahraničních investic; determinanty přímých zahraničních investic; vícenásobná regresní analýza.